Pensamento objetivo e sistema da razão pura (Revista Eletrônica Estudos Hegelianos, 2017)
ABSTRACT: The concept of science and its deduction are the outcome of the exposition of consciousness’ experience – the Phenomenology of Spirit. Such itinerary of consciousness brought forth absolute knowledge in which the opposition between subject and object was sublated. In this process, when self-consciousness recognizes the illusion of the separation between self-certainty and the truth of the object, there emerges the concept of science, which is the truth of consciousness – acknowledging that thought and being coincide. By sublating the opposition of consciousness, Hegel poses objective thinking, which becomes the content itself and aim of philosophy. By his concept of “objective thinking” – namely, thinking which can refer to the content of the thing itself (Sache selbst) and thus grasp (begreifen) it – Hegel intends to clarify that thought ought to cut off the ties with its representative trend. Objective thinking is the one which can go beyond mere subjective determinations and grasp the freedom of the objectivity of the thing. Through such itinerary Hegel conceives of the Science of Logic as the ‘system of pure reason’ – the organon of knowledge which clarifies the development of immanent determinations of thought. The present paper intends to discuss the position (Setzung) of the presuppositions (Voraussetzungen) of objective thinking, aiming to establish a brief relation between Kant’s and Hegel’s philosophy, in order to elucidate the project of the Logic as the Hegelian system of pure reason.